Early Colonization with a Group of Lactobacilli Decreases the Risk for Allergy at Five Years of Age Despite Allergic Heredity - Johansson, Maria A. (Public Library of Science, 2011)
BACKGROUND: Microbial deprivation early in life can potentially influence immune mediated disease development such as allergy. The aims of this study were to investigate the influence of parental allergy on the infant gut colonization and associations between infant gut microbiota and allergic disease at five years of age. METHODS AND FINDINGS: Fecal samples were collected from 58 infants, with allergic or non-allergic parents respectively, at one and two weeks as well as at one, two and twelve months of life. DNA was extracted from the fecal samples and Real time PCR, using species-specific primers, was used for detection of Bifidobacterium (B.) adolescentis, B. breve, B. bifidum, Clostridium (C.) difficile, a group of Lactobacilli (Lactobacillus (L.) casei, L. paracasei and L. rhamnosus) as well as Staphylococcus (S.) aureus. Infants with non-allergic parents were more frequently colonized by Lactobacilli compared to infants with allergic parents (p = 0.014). However, non-allergic five-year olds acquired Lactobacilli more frequently during their first weeks of life, than their allergic counterparts, irrespectively of parental allergy (p = 0.009, p = 0.028). Further the non-allergic children were colonized with Lactobacilli on more occasions during the first two months of life (p = 0.038). Also, significantly more non-allergic children were colonized with B. bifidum at one week of age than the children allergic at five years (p = 0.048). CONCLUSION: In this study we show that heredity for allergy has an impact on the gut microbiota in infants but also that early Lactobacilli (L. casei, L. paracasei, L. rhamnosus) colonization seems to decrease the risk for allergy at five years of age despite allergic heredity.